The specificities of the feasibility study of the ANUBiH project General Encyclopedia of Bosnia and Herzegovina - Miloš Trifković (Miroslav Krleža Institute of Lexicography, 2021)
The first two volumes of ethnically or territorially specific encyclopedias, the Croatian Encyclopedia of Bosnia and Herzegovina and Encyclopedia of the Republika Srpska, opened the issue of creating a General Encyclopedia of Bosnia and Herzegovina among the intellectual public. This encyclopedia should observe B&H as a complete, unique, and separate historical, social, and state entity based solely on scientifically established facts. The Presidency decided to engage ANUBiH in this project. After a phase of preparatory activities, the Academy concluded that existing socio-political conditions require a comprehensive feasibility study for the entire publishing endeavour, focused on the national general encyclopedia. This paper is the first response to that request. Based on the existing knowledge on feasibility studies and encyclopedistics and the current and anticipated social circumstances, the study determines the most important elements of the future feasibility study for the ANUBiH project General Encyclopedia of Bosnia and Herzegovina.